Thermal Adsorption and Corrosion Characteristic Study of Copper Hybrid Nanocomposite Synthesized by Powder Metallurgy Route - V. Senthilkumar; A. Nagadeepan; Melvin Victor De Poures; R. Sasikumar; N. Mukilarasan; M. Aruna; C. B. Priya; Gopal Kaliyaperumal; Elangomathavan Ramaraj (Adsorption Science & Technology)
Novel constitutions of ceramic bond the new opportunity of engineering materials via solid-state process attaining enhanced material characteristics to overcome the drawback of conventional materials used in aquatic applications. The copper-based materials have great potential to explore high corrosion resistance and good thermal performance in the above applications. The main objectives of this research are to develop and enhance the characteristics of the copper-based hybrid nanocomposite containing different weight percentages of alumina and graphite hard ceramics synthesized via solid-state processing (powder metallurgy). The presence of alumina nanoparticles with a good blending process has to improve the corrosion resistance, and graphite nanoparticles may limit the weight loss of the sample during potentiodynamic corrosion analysis. The developed composite’s micro Vickers hardness is evaluated by the E384 standard on ASTM value of 69 Hv and is noted by increasing the weight percentages of alumina nanoparticles. The conduction temperature of actual sintering anticipates the thermogravimetric analysis of developed composite samples varied from 400°C to 750°C. The thermogravimetric graph illustration curve of the tested sample found double-step decomposition identified between 427°C and 456°C. The potentiodynamic analyzer is used to evaluate the corrosion behaviour of the sample and the weight loss equation adopted for finding the theoretical weight loss of the composite.